2011
DOI: 10.2174/156720211798121034
|View full text |Cite
|
Sign up to set email alerts
|

HSP22 and its Role in Human Neurological Disease

Abstract: HSP22 (heat shock protein 22), belonging to the superfamily of small heat shock proteins, which has a molecular mass of 21.6 KD and is able to exist in the form of monomer, has multiple functions including molecular chaperones, apoptosis and anti-apoptosis, lifespan extension, antioxidation and so on. In recent years, studies show that HSP22 plays a crucial role in many neurological diseases, such as hereditary nerve endings disease, Alzheimer disease and Charco-Marie-Tooth. This review explores the progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Apoptosis is a form of the process of inducing programmed cell death that is induced by gene expression to maintain homeostasis under certain physiological and pathological conditions [ 44 ]. Previous studies have shown that LPS-induced cognitive impairment is related to apoptosis [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is a form of the process of inducing programmed cell death that is induced by gene expression to maintain homeostasis under certain physiological and pathological conditions [ 44 ]. Previous studies have shown that LPS-induced cognitive impairment is related to apoptosis [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Phosphorylation or mutation in definite sites of HspB8 leads to the development of clinical diseases, such as hereditary nerve ending disease, Charcot-MarieTooth, desmin-related cardiomyopathy, and breast cancer. [16][17][18][19][20] Failure to regulate the amyloid-beta peptide aggregation of HspB8 could cause the development of classic senile plaques in Alzheimer's disease. 21 HspB8 also has an important function in the stress reaction due to cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%